Complexity of the human T lymphocyte-specific cell surface antigen T3. - Jannie Borst; Mary Ann Prendiville; Cox Terhorst (1982)
A human T lymphocyte cell surface antigen T3 was found to be involved in several functions that were specific for the cells that express this marker on their surface. We show here that several glycoproteins were found in the immunoprecipitates prepared with a monoclonal reagent anti-T3. In addition to the major glycoprotein complex of 20 kd, glycoproteins of 25 to 28 kd, 37 kd, and 44 kd were detected in immunoprecipitates. The charge heterogeneity of the 20 kd and 25 to 28 kd proteins was caused by variable sialic acid content. The 20-kd T3 glycoprotein carried several "complex-type" and endoglycosidase-H-sensitive sugar moieties. We found that the 20-kd protein could be labeled with 125I-iodonaphthylazide, a reagent that reacts with hydrophobic areas of proteins.